Anxiety and Sleep Quality of COVID-19 Patients Treated in Dedicated COVID Hospitals - Shahin, Md; Hossain, Irin (Journal of Preventive and Social Medicine, 2025)
Background: COVID-19 pandemic in 2020 is associated with a high rate of anxiety and poor sleep quality among COVID-19 patients. The study aimed to assess the level of anxiety and sleep quality of COVID-19 patients treated in dedicated COVID hospitals. Methods: This multi-center cross-sectional study was conducted in Dhaka during the period of January to December 2020, in three dedicated COVID hospitals of Dhaka. A total of 306 COVID-19 patients were selected purposively from these hospitals according to their bed ratio. Coronavirus Anxiety Scale (CAS) and the Pittsburgh Sleep Quality Index (PSQI) were used to assess anxiety and sleep quality. Results: Among the participants, almost 87.0% were male and the majority were within 51 to 60 years of age. About 88.6% patients stayed in hospital for 1-10 days. Half of the participants had some kind of chronic disease. Among them, 31.0% participants had DM and 29.7% had HTN. 80.6% participants had no smoking history. About 38.2% participants had COVID-19 associated dysfunctional anxiety and 87.9% participants were associated with poor sleep quality. Almost 90.6% participants, those who had good sleep quality had COVID-19 dysfunctional anxiety and only 9.4% those who had good sleep quality had COVID-19 dysfunctional anxiety. Conclusion: This study suggests that there is a wide range of the Bangladeshi residents who are at higher risk of anxiety and poor sleep quality during COVID-19 pandemic. Policymakers and mental healthcare provider are advised to provide continuous monitoring of the psychological consequences during pandemic, and provide mental support. JOPSOM 2024; 43(1): 8-14